Chemotherapeutics potential of matcha green tea(Camellia sinensis (L.) Kuntze) on weri-Rb-1 retinoblastoma cancer cells - Sayuti, Nor Hafiza (2022)
Retinoblastoma is a childhood eye cancer that affects approximately 8,200 children each year. There is a paucity of published studies for retinoblastoma, specifically in Malaysia. Natural plants are widely used as alternative medicine in developed and developing countries. Camellia sinensis (matcha green tea) has been used as a traditional medicine to treat various diseases in Southeast Asia. However, their efficacy against retinoblastoma cancer has not been thoroughly investigated and characterized. The main objective of this study was to reveal the new insight on chemotherapeutics potential of matcha green tea extract (MGTE) against WERI-Rb-1, human retinoblastoma cells. Firstly, the optimized extraction condition of MGTE was determined through Response Surface Methodology (RSM) that aimed high amount of polyphenol compounds. The identification and quantification of polyphenol were performed via High- Performance Liquid Chromatography (HPLC). The highest polyphenol and antioxidant content yield were reached at a temperature of 80 °C, an extraction time of 20 min, a liquid-to-solid ratio of 100 mL/g. The HPLC analysis at the optimum extraction condition revealed 14 polyphenol compounds in MGTE. The chemotherapeutics potential of optimized MGTE was assessed in vitro through two different types of cultures: two dimensional (2D) and three dimensional (3D) cultures of WERI-Rb-1. Normal epithelial retina, ARPE-19 cell lines are used as a positive control. In vitro analysis for 2D cultured cells was performed on cytotoxicity assay, morphological studies, cell cycle, apoptosis analysis and gene expression studies. MGTE extract showed promising chemotherapeutics effect on WERI-Rb-1 cells. The treatment of MGTE showed low cytotoxicity (IC50 > 200 μg/mL) toward ARPE-19 cells but high cytotoxicity on WERI-Rb-1 with IC50 13.3 ± 1.40 μg/mL after 72 hours. MGTE induced apoptosis cell death rather than necrosis and caused arrest in the sub G0 phase, probably due to DNA fragmentation. Cell cycle analysis also proved that MGTE induced apoptotic cell death in the sub G0 phase. The chemotherapeutics effect of MGTE occurred via extrinsic and intrinsic apoptosis pathway by the activation of caspase 3, caspase 8, caspase 9, Bad and Bax that culminated in the apoptosis of WERI-Rb-1 cells. The chemotherapeutics potential of MGTE was further assessed in vitro through the 3D culture of WERI-Rb-1. The 3D collagen WERIRb- 1 cells were successfully developed using collagen type I as their extracellular matrix. The chemotherapeutics effect of MGTE on WERI-Rb-1 3D culture was investigated through cytotoxicity assay, morphological, gene and protein expression studies. The IC50 of MGTE on 3D collagen WERI-Rb-1 cells at 72 hours was higher in 3D culture cell with 64.41 ± 2.5 μg/mL. The treatment of MGTE cause a decrease in cell viability as the concentration increased as observed with DAPI/PI staining. The Scanning Electron Microscope (SEM) images showed the distinct morphological surface of 2D and 3D WERI-Rb-1 cells. MGTE and cisplatin-treated cells showed characteristics of apoptotic cell death. Treatment with MGTE on WERI-Rb-1 cells caused upregulation of proapoptotic proteins, thus resulting in apoptosis cell death. The gene and protein expression revealed the induction of extrinsic and intrinsic apoptosis pathways mediated by MGTE through expression of bax, caspase 3, caspase 8 and caspase 9 protein in 3D collagen WERI-Rb1 cells. However, 72 hours of MGTE treatment also induced the expression of Nrf2, HO-1, and SOD1 proteins, this likely decreased the sensitivity of WERI-Rb-1 cells toward MGTE treatment in the 3D culture system of WERI-Rb-1 cells. The upregulation of antioxidant proteins may provide cryoprotection for 3D collagen WERI-Rb-1 cells towards MGTE treatment. Despite the observed expression of Nrf2, HO-1, and SOD1 proteins, MGTE showed the ability to activate apoptosis cell death in 3D collagen WERI-Rb-1 cells. In conclusion, the findings suggest the new chemotherapeutic potential of MGTE in inducing apoptosis cell death in both 2D and 3D culture systems. This finding can be used as the fundamental understanding and new knowledge of the chemotherapeutics potential of matcha green tea extract specifically on retinoblastoma cancer cells.